2017
DOI: 10.32473/edis-wc174-2017
|View full text |Cite
|
Sign up to set email alerts
|

Talking Local: Florida Consumer Definitions of Local Food

Abstract: This is a minor revision of an EDIS publication focusing on consumer definitions of local food. It is the first in the  Talking Local series, a six-part EDIS publication series about Florida consumers and their perceptions of local food. This series focuses on ways Extension agents can assist Florida farmers and ranchers in the labeling, sale, and promotion of locally produced products. This series provides information about Florida consumers’ perceptions of local food to Extension faculty who are interested i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Research even suggests that when consumers in developing countries are faced with the choice of making consumption decisions between local brands and nonlocal or foreign brands, the decision is inclined towards foreign brands (Yasin et al , 2007; Ar and Kara, 2014). Literature has shown that people have different understandings of what local means, according to where they live and the types of products available (Roper et al , 2015). Henceforth, local can be defined by physical location and personal connection (Trivette, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Research even suggests that when consumers in developing countries are faced with the choice of making consumption decisions between local brands and nonlocal or foreign brands, the decision is inclined towards foreign brands (Yasin et al , 2007; Ar and Kara, 2014). Literature has shown that people have different understandings of what local means, according to where they live and the types of products available (Roper et al , 2015). Henceforth, local can be defined by physical location and personal connection (Trivette, 2015).…”
Section: Introductionmentioning
confidence: 99%